2016
DOI: 10.3892/mco.2016.1106
|View full text |Cite
|
Sign up to set email alerts
|

Typing of killer-cell immunoglobulin-like receptors and their cognate human leukocyte antigen class I ligands predicts survival of Chinese Han patients with metastatic non-small-cell lung cancer

Abstract: Abstract. Non-small-cell lung cancer (NSCLC) may establish an immunosuppressive tumor microenvironment that is conducive to tumor growth. Natural killer (NK) cells play a pivotal role in immunological surveillance. Activation of NK cells partially depends on the interactions between killer-cell immunoglobulin-like receptors (KIRs) and human leukocyte antigen (HLA) class I ligands. We herein investigated the association of KIRs and HLA ligands with survival in metastatic NSCLC (mNSCLC) patients treated with che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It has been reported that the average OS of advanced stage HCC patients who did not receive systematic treatments was merely 7.1 months . To date, the molecular biological mechanisms affecting the progression and prognosis of HCC have not been fully illuminated . From the point of view of clinical practice, exploration of molecular biological mechanisms affecting the prognosis of HCC and identification of reliable prognostic biomarkers are valuable for optimizing individualized treatments and improving clinical prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the average OS of advanced stage HCC patients who did not receive systematic treatments was merely 7.1 months . To date, the molecular biological mechanisms affecting the progression and prognosis of HCC have not been fully illuminated . From the point of view of clinical practice, exploration of molecular biological mechanisms affecting the prognosis of HCC and identification of reliable prognostic biomarkers are valuable for optimizing individualized treatments and improving clinical prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with these results, patients with the KIR2DL2 + /KIR2DS2 + - C1C1 genotype survived longer than others ( P =0.009) 13. However, Yu et al did not observe any relationship between HLA/KIR combinations and response to treatment in NSCLC in a Chinese Han population 14. Here, we did not examine the response to NSCLC treatment, which is one of limitations of the current study; thus, we could not compare our results with others.…”
Section: Discussionmentioning
confidence: 56%
“…In 2010, Al Omar et al 17 reported that there were no significant differences in the proportion of patients with different KIR genes, genotypes and haplotypes among patients with solid tumors (NSCLC, small-cell lung cancer, colon cancer and kidney cancer). Then, Yu et al reported the KIR gene frequency showed no differences between NSCLC and healthy controls in a Chinese Han population 14. Also Wiśniewski et al 13 did not find such differences in Polish Caucasians.…”
Section: Resultsmentioning
confidence: 96%
“…In the present study, Luminex bead-based multiplex assays (Bio-Rad Laboratories, Inc., Hercules, CA, USA) were used to measure the levels of 22 cytokines in the plasma of patients with metastatic NSCLC receiving platinum-based chemotherapy in a Chinese cohort from the Fudan University Shanghai Cancer Center (FUSCC) study. In this cohort, the impact of innate immune parameters (natural killer lymphocyte phenotype) on patient survival was previously analyzed (18). The objective of the present study was to evaluate various plasma cytokine levels, T-helper (Th)1/Th2 cytokine ratios, pro-/anti-inflammatory factor ratios and other patient characteristics as prognostic factors with a significant impact on OS and PFS.…”
Section: Elevated Il-6/il-1ra Ratio As a Prognostic Biomarker Of Poormentioning
confidence: 99%
“…101192-9 in the Fudan University Shanghai Cancer Center Ethical committee register. (18). Patient recruitment lasted for 7 months and the patients were followed for OS and PFS during at least 2 years, with a median follow-up time of 28 months.…”
Section: Study Design and Patientsmentioning
confidence: 99%